Synthesis of Headful Packaging Phages Through Yeast Transformation-Associated Recombination - Cheng Lu; Lan He; Yangyijun Guo; Tingting Wang; Yanrui Ye; Zhanglin Lin (Viruses)
De novo synthesis of phage genomes enables flexible genome modification and simplification. This study explores the synthetic genome assembly of Pseudomonas phage vB_PaeS_SCUT-S4 (S4), a 42,932 bp headful packaging phage, which encapsidates a terminally redundant, double-stranded DNA genome exceeding unit length. We demonstrate that using the yeast TAR approach, the S4 genome can be assembled and rebooted from a unit-length genome plus a minimal 60 bp terminal redundant sequence. Furthermore, we show that S4 can be synthesized from arbitrary starting nucleotides and modified with a red fluorescent protein as a reporter. Additionally, we successfully designed and assembled synthetic S4 phages with reduced genomes, knocking out up to 10 of the 24 hypothetical genes simultaneously, with a combined length of 2883 bp, representing 6.7% of the unit-length genome. This work highlights the potential for engineering simplified, customizable headful packaging phage genomes, providing a foundation for future studies of these phages for potential clinical applications.